Synthesis of highly crystalline imine-linked covalent organic frameworks via controlling monomer feeding rates in an open system. Issue 88 (19th October 2022) - Wang, Xueqing; Liu, Manying; Wang, Xiaoyan; Tan, Bien
Abstract : Covalent organic frameworks (COFs) have enormous potential in various applications because of their high crystallinity and superior surface area. Abstract : Covalent organic frameworks (COFs) have enormous potential in various applications because of their high crystallinity and superior surface area. However, it is still challenging to synthesize crystalline COFs using a convenient and effective synthetic strategy. Herein, we report a strategy to synthesize four highly crystalline imine COFs, namely, TATB-DATP-COF, PDA-TAPB-COF, OMePDA-TAPB-COF and COF-320, by polymerization with a dropwise monomer feeding method in an open system, without using additional templates or modulators. By controlling the feeding rates of the monomer, the reversibility of imine formation, defect self-healing and error correction can be improved.